KONSTRUKSI SOSIAL ISLAM MODERAT JAMAAH MAIYAH MOCOPAT SYAFAAT PADA GENERASI MILENIAL DI YOGYAKARTA - Najib, Khotim Hanifudin; Habibullah, Achmad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
Understanding moderate Islam is very important to millennial Muslim generations in Indonesia. Today, this millennial generation is threatened by exposure to radicalism and intolerance, such as environmental studies, reading books and the Internet. This paper is a phenomenological study of the recitation of the congregation of intercessors Maiyah mocopat to inculcate moderate Islamic understanding in the millennial generation in Yogyakarta. The externalization of moderate Islam towards the millennial generation is achieved by creating a comfortable and enjoyable learning environment. Activities that occurred during this interfaith prayer session included Al-Quran, Shalawatan, Group Discussions, delivery of resource materials, sharing, and events interspersed with Kyai Kanjeng music performances. The activity makes the millennial generation have an objective understanding (objectivation) about peaceful Islam, soothing Islam, and moderate Islam. The internalization of moderate Islam is carried through primary socialization and secondary socialization. Primary socialization is carried in the family environment with the exemplary method. Whereas secondary socialization is carried in educational institutions such as schools, recitals, including through interfaith recitation sessions which held every 17th of the month